Hyperbaric Oxygen Therapy for Scleroderma Wounds: A Report on Two Cases and Literature Review - Chih Yu Fang; Kevin D. Kerin; Jay C. Buckey (Annals of Internal Medicine: Clinical Cases)
Systemic sclerosis-associated wounds are often refractory to conventional wound care and pharmacotherapy. Hyperbaric oxygen (HBO2) therapy has a longstanding, yet infrequently documented, history of success healing wounds in patients with systemic sclerosis. Here, we present 2 cases of scleroderma-associated cutaneous wounds, unresponsive to standard treatments, successfully treated with HBO2. Additionally, we reviewed the current literature for articles that used HBO2 adjunctively with wound care in systemic sclerosis. These published studies showed an overall success rate of 81%.